Dimensi Perancangan Kota pada Ruang Publik (Studi Kasus: Kawasan Alun – Alun Hanggawana Slawi) - Muhammad Azmy Ikhsani; Artanti Kusuma Ayu; Safety Husna Pangestika (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2025)
Hanggawana Square in Slawi has an important role in shaping the city's identity and improving the quality of public spaces. This study aims to analyse the urban design dimensions that shaped the area around Hanggawana Square in Slawi after its revitalisation in 2017. The descriptive qualitative approach uses direct observation at the location and a literature study as secondary data. The results show that the square is composed of several urban design dimensions: morphological, functional, social, visual, perceptual, and temporal. The morphological dimension is reflected in the radial pattern of the roads and the prevalence of land designated for offices. This area is used for government activities, recreation, and the informal economy. The social dimension is evident in the high intensity of public interaction, particularly during car free day activities. Visually, landmark elements such as Pendopo Amangkurat and public artworks strengthen the city’s image. Perceptually, users consider this area comfortable, safe, and accessible. The temporal dimension of Alun-Alun Hanggawana is evident in the buildings that have existed over time, as well as in the various activity patterns that occur in the area. This study shows that integrating the overall dimensions of urban design is key to creating inclusive, representative, and characterful public spaces.